LEFT ATRIUM THROMBOSIS IN PATIENTS WITH RHEUMATIC MITRAL VALVULAR DISEASE - N. D. Kaverin; O. A. Hrustalev (Klinicist)
Systemic thromboembolism — fairly common complication of mitral valvular disease, often leading to disability or fatal consequences for the patient. The source of emboli in most cases, are blood clots localized in the left atrium. The survey reflected basic views on the pathogenesis, diagnosis, treatment and prevention of intraatrial thrombosis according to new scientific advances. Articles (reviews, meta-analyzes and original researchs) from Pub Med database, as well as domestic literature were used.